Body mass index modified the effectiveness of low dose aspirin treatment on frozen-thawed embryo transfer outcome: a propensity score-matched study - Chen, Kaijie; Cai, Jiali; Tong, Jie; Liu, Lanlan; Liu, Zhenfang; Chen, Jinhua; Yang, Xiaolian; Yang, Chao; Geng, Jie; Ma, Caihui; Ren, Jianzhi; Jiang, Xiaoming (Frontiers in Endocrinology, 2024)
Background Low-dose aspirin is one of the widely used adjuvants in assisted reproductive technologies with the hope of improving the live birth rate. However, the studies regarding its effects are conflicting. The study aimed to investigate the association between aspirin administration and live birth following frozen-thawed embryo transfer (FET) in patients with different body mass index (BMI). Methods A retrospective cohort study was performed on 11,993 patients receiving FET treatments. 644 of which received a low-dose aspirin (100 mg/day) during endometrial preparation until 10 weeks after transfer. Propensity score matching was performed to avoid selection biases and potential confounders. Results The clinical pregnancy rate and live birth rate were similar before matching (54.4% versus 55.4%, RR: 1.02, 95%CI: 0.95-1.09, and 46.3 versus 47.8, RR: 1.03, 95%CI: 0.95-1.12 respectively). A weak association in favor of aspirin administration was found in the matched cohort (49.5% versus 55.4%, RR: 1.12, 95%CI: 1.01-1.24, and 41.9% versus 47.8%, RR: 1.14, 95%CI: 1.01-1.29 respectively). However, when stratified the patients with WHO BMI criteria, a significant increase in live birth rate associated with aspirin treatment was found only in patients with low BMI (<18.5 kg/m2) in either unmatched (46.4% versus 59.8%, RR:1.29, 95%CI:1.07-1.55) or matched cohort (44% versus 59.8%, RR: 1.36, 95%CI: 1.01-1.83) but not in patients with higher BMI categories. With the interaction analysis, less association between aspirin and live birth appeared in patients with normal BMI (Ratio of OR:0.49, 95%CI: 0.29-0.81) and high BMI (Ratio of OR:0.57, 95%CI: 0.27-1.2) compared with patients with low BMI. Conclusion BMI may be considered when evaluating aspirin’s effect in FET cycles.